PERANAN SOUND SYSTEM TERHADAP ESTETIKA PERTUNJUKAN WAYANG KULIT PURWA: STUDI KASUS PERGELARAN WAYANG KI PURBO ASMORO - Finarno, Hannova Aji; Santoso, Iwan Budi (Institut Seni Indonesia Surakarta, 2024)
This study examines the role and influence of the sound system in Ki Purbo Asmoro’s ancient shadow puppet performance. Research studies answer three basic questions as the formulation of research problems, namely (1) How the concept of sound in the wayang purwa performance? (2) What are the sound system devices for amplification and how is it applied in wayang purwa performances? and (3) What is the role and function of using a sound system in a puppet show? prototype? This type of research uses a qualitative descriptive approach, with data collection through interview with resource persons, literature study and observation. Results Research shows that the use of sound system technology in performances wayang purwa with the puppeteer Ki Purbo Asmoro not only for the sake of amplify sound. Utilization by means of microphones, audio mixers and equalizer is done to amplify the sound. Sound reinforcement in the sense of wayang performances don’t have to be loud, but the strength of the sound can mean sound clear and/or clear sound.